Efektivitas Strategi Digital Marketing di Media Sosial: Studi Kasus Facebook, Instagram, dan Tiktok Generasi Z - Sahata Sitanggang, Andris; Naufal Nazhif, Dhafin; Harits Ar-Razi, Muhammad; Anugrah Febrian Buaton, Marcell (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The objective of this study is to analyze the factors that have contributed to the rapid growth of digital marketing on social media, evaluate the importance of digital marketing in the context of social media in the digital age, and identify efficient strategies for implementing digital marketing on social media. The research methodology employed included a quantitative research design with a questionnaire distributed to Generation Z respondents. The data were analyzed using statistical analysis software to assess the efficacy of digital marketing strategies on various social media platforms, including Facebook, Instagram, and TikTok. The findings of the study indicate that Instagram and TikTok are more effective in attracting the attention and engagement of Generation Z than Facebook. Instagram demonstrated the highest level of engagement with visual content, while TikTok exhibited a clear advantage in terms of interactive short video content. The primary factor influencing efficacy is the provision of informative and relevant content aligned with individual interests. The most effective digital marketing strategy entails the use of creative and interactive content on TikTok and Instagram platforms. In conclusion, the results indicate that TikTok and Instagram are more effective than Facebook in attracting the attention of and engaging with Generation Z. The use of visual, interactive, and authentic content is a key factor in the success of digital marketing strategies on these platforms. This study provides guidance for marketers in selecting effective social media platforms and designing digital marketing strategies to reach Generation Z audiences.